Performance Investigation on Scan-On-Receive and Adaptive Digital Beam-Forming for High-Resolution Wide-Swath Synthetic Aperture Radar - Bordoni, F.; Younis, M.; Varona, E. Makhoul; Gebert, N.; Krieger, Gerhard (International ITG Workshop of Smart Antennas, 2009)
The work investigates the performance of the Smart Multi-Aperture Radar Technique (SMART) Synthetic Aperture Radar (SAR) system for high-resolution wide-swath imaging based on Scan-on-Receive (SCORE) algorithm for receive beam steering. SCORE algorithm works under model mismatch conditions in presence of topographic height. A study on the potentiality of an adaptive approach for receive beam steering based on spatial spectral estimation is presented. The impact of topographic height on SCORE performance in different operational scenarios is examined, with reference to a realistic SAR system. The SCORE performance is compared to that of the adaptive approach by using the Cramèr Rao lower bound analysis.
DLR Import::2019-04-03